43. EVALUATION OF THE PAIN RELIEF EFFECTIVENESS OF ELECTROACUPUNCTURE AT “JAJIE” POINTS COMPARED TO ELECTROACUPUNCTURE AT “YUAN-LUO” POINTS IN PATIENTS WITH LOW BACK PAIN FROM SPINAL DEGENERATION (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluation of the pain relief effectiveness of electroacupuncture at “jajie” points and electroacupuncture at “yuan-luo” points in patients with low back pain from spinal degeneration.Subject and methods: A descriptive cross-sectional study, combined to evaluate the treatment effectiveness of two electroacupuncture methods in patients with low back pain from spinal degeneration. A total of 88 patients were randomly assigned to two groups (group 1 is electroacupuncture at “jajie” points, group 2 is electroacupuncture at “yuan-luo” points).Results: After 14 days of treatment, the VAS score decreased significantly with group 1 from 6.25 ± 0.58 to 2.41 ± 0.79 and group 2 from 6.46 ± 0.59 to 2.00 ± 0.72. According to the survey, the VAS score, the Schober index and the hand - soil index improved significantly in 2 groups compared to before treatment (p < 0.001). The difference between two groups was statistically significant (p < 0.05).Conclusions: Electroacupuncture at “yuan-luo” points showed better pain relief effect compared to electroacupuncture at “jajie” points in patients with low back pain from spinal degeneration.
Keywords: Low back pain; spinal degeneration; electroacupuncture at “jajie” points; electroacupuncture at “yuan-luo” points